1979
DOI: 10.2170/jjphysiol.29.427
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Active Motor Units and Their Firing Rates in Voluntary Contraction of Human Brachialis Muscle

Abstract: Voluntary contraction of the skeletal muscles is controlled by two mechanisms : One changes the number of active motor units and the other changes the firing rate of individual motor units. It has been generally believed that the former is the main factor in coarse control and the latter in fine control. Recently, MILNER-BROWN et al. (1973 a, b) investigated quantitatively the relation between motor unit activity and voluntary isometric force in the human first dorsal interosseus muscle and concluded that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 14 publications
3
52
0
Order By: Relevance
“…Baldissera, Gustafsson & Parmiggiani (1978) have accounted for this effect (the so-called secondary range of motoneurone firing) by a model based on the time course of motoneuronal after-hyperpolarization, indicating that it may well be a passive response to high levels of synaptic current injection. This effect may also account for the extremely rapid firing-rate bursts (60-120/sec) seen by Desmedt & Godaux (1977) (Kanosue et al 1979) has demonstrated behaviour similar to that seen here in the deltoid, but with an increased reliance on rate coding above 70 % m.v.c. Our study did not investigate the force range between 80 and 100 % m.v.c.…”
Section: Motor Unit Beha Viour In Different Musclessupporting
confidence: 73%
“…Baldissera, Gustafsson & Parmiggiani (1978) have accounted for this effect (the so-called secondary range of motoneurone firing) by a model based on the time course of motoneuronal after-hyperpolarization, indicating that it may well be a passive response to high levels of synaptic current injection. This effect may also account for the extremely rapid firing-rate bursts (60-120/sec) seen by Desmedt & Godaux (1977) (Kanosue et al 1979) has demonstrated behaviour similar to that seen here in the deltoid, but with an increased reliance on rate coding above 70 % m.v.c. Our study did not investigate the force range between 80 and 100 % m.v.c.…”
Section: Motor Unit Beha Viour In Different Musclessupporting
confidence: 73%
“…However, entry into the primary range following subprimary range discharge should be considered as an alternative explanation for ratelimiting discharge patterns. Particularly at low forces, a subprimary-primary range pattern of activation would achieve efficient modulation of motor-unit force while reserving secondary range modulation for more intense efforts, as suggested by some studies of motor-unit activity (Kanosue et al 1979).…”
Section: Subprimary Range In Rat Hindlimb Motoneuronsmentioning
confidence: 99%
“…The central nervous system achieves a precise and task-specific control of skeletal muscle forces by controlling the number of activated motor units (recruitment) and the firing frequency of the activated motor units (rate-coding) (Kamen and Du, 1999;Kanosue et al, 1979). In individuals with paralysis due to upper motor neuron dysfunction, electrical stimulation is used to substitute for the loss of voluntary motor control to enable patients to stand, walk, and grasp objects (Kralj et al, 1988;Liberson et al, 1961).…”
Section: Introductionmentioning
confidence: 99%